2017
DOI: 10.1038/s41598-017-05770-7
|View full text |Cite
|
Sign up to set email alerts
|

Naja sputatrix Venom Preconditioning Attenuates Neuroinflammation in a Rat Model of Surgical Brain Injury via PLA2/5-LOX/LTB4 Cascade Activation

Abstract: Inflammatory preconditioning is a mechanism in which exposure to small doses of inflammatory stimuli prepares the body against future massive insult by activating endogenous protective responses. Phospholipase A2/5-lipoxygenase/leukotriene-B4 (PLA2/5-LOX/LTB4) axis is an important inflammatory signaling pathway. Naja sputatrix (Malayan spitting cobra) venom contains 15% secretory PLA2 of its dry weight. We investigated if Naja sputatrix venom preconditioning (VPC) reduces surgical brain injury (SBI)-induced ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In this study, we focused on understanding the contribution of kynurenine pathway to perisurgical site injury after SBI. Various cytokines and inflammatory mechanisms are activated following SBI (Sherchan et al, ; Wang et al, ), which can stimulate KMO and thereby upregulate the downstream release of the neurotoxic QUIN. We first measured the endogenous expression of QUIN and KYNA in the perisurgical brain tissue following SBI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on understanding the contribution of kynurenine pathway to perisurgical site injury after SBI. Various cytokines and inflammatory mechanisms are activated following SBI (Sherchan et al, ; Wang et al, ), which can stimulate KMO and thereby upregulate the downstream release of the neurotoxic QUIN. We first measured the endogenous expression of QUIN and KYNA in the perisurgical brain tissue following SBI.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in neuronal apoptotic proteins with wnt3a administration was associated with significant neurobehavior improvement in forelimb placement and recovery of modified Garcia scores to sham levels. Studies have shown that MCAO causes deleterious neurological effects on modified Garcia (Wang et al, 2017) and left forelimb placement (Senda et al, 2011), tests that correlate with cerebral infarction. We examined the neuropathological damage at 24 and 72 h after MCAO and found our model to create significant neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…In the following sections, we expand on the concept of preconditioning and propose the use of venom-derived proteins as a preconditioning therapy for SBI. [35,44,45,67,68], it has often been noted that clinical translation is limited since many injuries occur spontaneously. In the last few decades, the potential of PC, especially for scheduled (or elective) surgeries, has become a real focus in hopes of developing an effective therapy.…”
Section: Neurotherapeutics and Preconditioning In Surgical Brain Injurymentioning
confidence: 99%
“…Investigators have been able to give insight into the pathology, cellular mechanism of action, and where areas of therapeutic focus should be for treating SBI. Now, with evidence supporting the efficacy of PC [34,67], the need remains to investigate a translational therapy. Because of the recent discoveries of snake venom PC and a further understanding of the mechanism driving these protective effects, we have focused our attention on specific venom protein components which we believe can provide protective effects for edema and hemorrhage.…”
Section: Neurotherapeutics and Preconditioning In Surgical Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation